Legal Analysis on the Valuation of A Company’s Shares Nominal Value - M.Y.F. Hafidz Nasution; Dwi Sartika Paramyta (IHSA Institute, 2022)
The existence of a Company as a legal entity with a commercial purpose in a state holds an important role in developing the national economy. Such existence must be supported with a comprehensive regulatory framework that able to ensure legal certainty of every legal action relating to a Company. The prevailing regulations relevant to a Company includes, among others, the valuation of a Company’s shares, which hold a significant role either to the Company itself, the shareholders, and other third parties, especially in investing into or doing a business activity. Therefore, this research is drafted to discuss the legal aspects in valuation of a Company’s shares in Indonesia. This research used a descriptive method with a qualitative approach.